Analisis Frasa “Menimbun Bara Api” terhadap Pembentukan Karakter: Kajian Hermeneutik Berdasarkan Kitab Amsal 25:21-22 - Pattinaja, Aska Aprilano; Sualang, Farel Yosua (Sekolah Tinggi Teologi Sumatera Utara, 2025)
Based on the literature review, there are two groups of scholars discussing Proverbs 25:21-22: the group that links the writing of this verse to Jesus' teachings on love and forgiveness, and the group that focuses only on the teachings of Paul, who quoted this verse as an exhortation to the Romans to do good to their enemies and that there is a reward for every good deed. The research attempts to examine to analyze the meaning of the phrase